Current research into A20 mediation of allergic respiratory diseases and its potential usefulness as a therapeutic target - Liu, Yan; Xu, Kai; Yao, Yin; Liu, Zheng (Frontiers in Immunology, 2023)
Allergic airway diseases are characterized by excessive and prolonged type 2 immune responses to inhaled allergens. Nuclear factor κB (NF-κB) is a master regulator of the immune and inflammatory response, which has been implicated to play a prominent role in the pathogenesis of allergic airway diseases. The potent anti-inflammatory protein A20, termed tumor necrosis factor-α-inducible protein 3 (TNFAIP3), exerts its effects by inhibiting NF-κB signaling. The ubiquitin editing abilities of A20 have attracted much attention, resulting in its identification as a susceptibility gene in various autoimmune and inflammatory disorders. According to the results of genome-wide association studies, several TNFAIP3 gene locus nucleotide polymorphisms have been correlated to allergic airway diseases. In addition, A20 has been found to play a pivotal role in immune regulation in childhood asthma, particularly in the protection against environmentally mediated allergic diseases. The protective effects of A20 against allergy were observed in conditional A20-knockout mice in which A20 was depleted in the lung epithelial cells, dendritic cells, or mast cells. Furthermore, A20 administration significantly decreased inflammatory responses in mouse models of allergic airway diseases. Here, we review emerging findings elucidating the cellular and molecular mechanisms by which A20 regulates inflammatory signaling in allergic airway diseases, as well as discuss its potential as a therapeutic target.